A cognitive-oriented exploration of the development of translation competence: a case study of Iranian translation learners - Komeili, Mustafa; Dabbaghi, Azizollah; Barati, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2019)
This is a report on a qualitative research in relation to the development of translation competence (TC) in academia. The study aimed to map out the cognitive processes involved in problem-solving and provide a picture of the development of strategic TC and translation-notion in translation learners. A group of 20 Iranian students volunteered to take part in a think-aloud study. The participants were divided into four groups of G1 (pretranslational), G3 (early translational), G5 and G7 (translational), based on the number of semesters of language and translation training they had received. The ecological validity was established by availing the participants of any sources of documentation they preferred to use. The verbalisations of the participants were recorded and then transcribed into think-aloud protocols (TAPs). The analysis of TAPs revealed that students activated various configurations of decision-making processes and resourcing methods, and exhibit different conceptions of the notion-of-translation at different stages of TC development. The study also showed that the portrait of TC development featured strong reliance on automatised cognitive processes at pre-translational stage and increased evaluative processes, coupled with higher chances of success, at translational stage. The findings proved that the development of TC did not follow an incremental trajectory. They further indicated that the translation programmes as offered in universities tend to boost evaluative reflections on and conscious awareness of the translation process at the cost of decreasing the unconscious automatised processes. This suggests that from a process-oriented perspective, translation programmes do not seem to prepare the learners for translation-market requirements.